Optimizing central pattern generators (CPG) controller for one legged hopping robot by using genetic algorithm (GA) - Hadi Azahar, Arman; Shin Horng, Chong; Mohamed Kassim, Anuar; Faiz Zainal Abidin, Amar; Haniff Harun, Mohamad; Badril Nor Shah, Mohd; Azha Mohd Annuar, Khalil; Manap, Mustafa; Ismael Rizman, Zairi (International Journal of Engineering and Technology, 2018)
This paper presents the optimization process of Central Pattern Generator (CPG) controller for one legged hopping robot by using Genetic Algorithm (GA). To control the one legged hopping robot, a CPG controller is designed and integrated with a conventional Proportional-Integral (PI) controller. Conventionally, the CPG parameters are tuned manually. But by using this method, the parameters produced are not exactly the optimum parameters for the CPG. Therefore, a computational stochastic optimization method; GA is designed to optimize the CPG controller parameters. The GA is designed based on minimizing the error produced towards achieving the reference height. The re-sponse of the one legged hopping robot is compared and the results of the error towards reference height are analyzed.Â Â
Keywords: One Legged; Hopping; CPG; PI; Genetic Algorithm